SPEECH DISORDER OF STUTTERING CHARACTER IN "ROCKET SCIENCE" MOVIE - Sari, Mayang Hima; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
AbstractStuttering is a speech disorder in which repetition and prolongation of syllables, sound, and phrase interfere with fluency. Someone who experiences stuttering will have a hard time to start the word because of disruption in repetition, vocals and articulation involve the throat, palate, tongue, lips, and teeth. Stuttering may be worse when the person is excited, tired or under stress, or when feeling self-conscious, hurried or pressured. A situation such as speaking in front of a group or talking to the phone can be particularly difficult for people who stutter. As a reflection of real life, a movie can also contain the phenomena of stuttering such as in Rocket Science movies. This research aimed to describe the types of stuttering and also the consequences of being stuttering in social life that experienced by Hal Hefner in Rocket Science movies. This research was conducted by using content analysis qualitative method. The data were generated from movie and movie script in the form of utterances, dialogues, words, and conversations. The result of this research shows that there are ninety-five data which are indicated as the types of stuttering experienced by Hal Hefner in Rocket Science movie. Besides, it was also found the consequences of being stuttering in social life experienced by Hal Hefner in the movie. The researcher shows that there are twelve data of consequences that the researcher found in the movie. The most common consequence that the researcher found in the film is fear to talk.  AbstrakGagap adalah gangguan berbicara yang mana terjadinya pengulangan dan perpanjangan suku kata, suara, dan frasa yang dapat menganggu kefasihan. Seseorang yang mengalami gagap akan mengalami kesulitan untuk memulai kata karena gangguan dalam pengulangan, vokal, dan artikulasi yang melibatkan tenggorokan, langit-langit mulut, lidah bibir, dan gigi. Gagap akan lebih buruk ketika bersemangat, lelah atau dibawah tekanan, atau ketika merasa sadar diri, tergesa-gesa atau tertekan. Situasi ketika berbicara didepan kelompok atau berbicara di telepon dapat menjadi sangat sulit bagi orang yag gagap. Sebagai cerminan dari dunia nyata, sebuah film juga mengandung fenomena kegagapan seperti dalam film Rocket Science. Penelitian ini bertujuan untuk mengidentifikasi jenis gagap dan juga konsekuensi dari kegagapan dalam kehidupan sosial yang dialami oleh Hal Hefner dalam film Rocket Science. Penelitian ini dilakukan dengan menggunakan analisis isi kualitatif. Data dihasilkan dari skrip film dan film dalam bentuk ucapan, dialog, kata-kata dan percakapan. Hasil penelitian ini menunjukan bahwa ada Sembilan puluh lima data yang diidentifikasi sebagai jenis gagap yang dialami oleh Hal Hefner dalam film Rocket Science. Selain itu, ditemukan juga konsekuensi kegagapan dalam kehidupan sosial yang dialami Hal Hefner dalam film tersebut. Peneliti menunjukkan bahwa ada dua belas data dari konsekuensi yang ditemukan oleh peneliti di dalam film. Konsekuensi yang paling banyak ditemukan dalam film tersebut adalah takut untuk berbicara.